CD8+tumor‐infiltrating lymphocytes at primary sites as a possible prognostic factor of cutaneous angiosarcoma. Issue 10 (18th November 2013) - Fujii, Hiroko; Arakawa, Akiko; Utsumi, Daisuke; Sumiyoshi, Shinji; Yamamoto, Yosuke; Kitoh, Akihiko; Ono, Masahiro; Matsumura, Yumi; Kato, Mayumi; Konishi, Keisuke; Shiga, Takeo; Sano, Shigetoshi; et al.
<x xml:space="preserve">Abstract</x> Tumor‐infiltrating lymphocytes (TILs) have been reported as a prognostic factor in various cancers and are a promising target for immunotherapy. To investigate whether TILs have any impact on the prognosis of angiosarcoma patients, 55 non‐treated patients (40 patients at stage 1 with cutaneous localized tumors, 4 patients at stage 2 with lymph node metastases and 11 patients at stage 3 with distant metastases) with angiosarcoma were evaluated retrospectively by immunohistochemistry stained CD4, CD8, FOXP3 and Ki67. The Kaplan–Meier method was used to estimate overall survival with patients at stage 1. Survival differences were analyzed by the log‐rank test. Patients with higher numbers of CD8+ TILs in their primary tumors survived significantly longer compared with patients with lower values. Moreover, the number of CD8 in TILs was positively correlated with a distant metastasis‐free period. The total number of primary TILs (CD4 plus CD8) and CD8+ primary TILs of stage 3 patients with distant metastases was positively correlated with their overall survival. To evaluate whether CD8+ effector T cells are activated or differentiated, flow cytometric analysis of peripheral blood mononuclear cells (PBMC) was performed. The percentages of CD8+ T cells producing IFN‐γ in PBMC were significantly higher in patients with angiosarcoma (n = 10) compared not only with that of healthy controls (n = 20) but also patients with advanced melanoma (n = 11). These results suggest that anti‐tumor immunity is clinically relevant in angiosarcoma.